Writing Tradition and Intellectual Heritage of Jambi Ulama - Zami, Rahyu; Gunawan, Hendra (Universitas Islam Negeri Sumatera Utara, 2025)
Ulama are very important figures in the writing tradition, and Islamic boarding schools are institutions where ulama produce many of their written works. As educational institutions, Islamic boarding schools have a crucial role in developing and strengthening Islamic intellectual traditions. Islamic boarding schools are also recognized as one of the institutions that effectively produces book writings for ulama, because Islamic boarding schools are a comfortable place for ulama to transmit their knowledge. The writings of scholars are generally handwritten using pure Arabic letters in Arabic and Arabic letters using Malay, Javanese or other regional languages, and studies in the broad Islamic studies section. This research uses historical methods through in-depth study and analysis of ulama books in Jambi. The findings in this research are, First, that Islamic boarding school ulama books are made in various types ranging from original books, translations, texts, summaries, adaptations and excerpts. Second, in general books written by ulama are used by the general public and used as teaching materials in Islamic boarding schools. Third, the work of the ulama and Islamic boarding school administrators is still used today with various uses, ranging from national, regional and local scopes.